Broadening the Business Discipline: Teaching the History of Business in the Faith Tradition - Bosch, David; Brown, Kevin; Gill, Mark (Christian Business Academy Review)
This paper aims to unite key business principles with theological insights for faculty within faithbased institutions of higher education. The purpose of this content is to illustrate what a classroom aiming to reflect on faith identity, commercial activity, and the history between them could be for prospective faculty. People of faith, like everyone else, are active participants in a business-dominated world. Developing a clear understanding of how the business world runs and, more importantly, having our faith perspective define and dictate how we conceive and behave within this world is the primary intent of such a class.